PENGARUH MEDIA SUSPENSI TERHADAP PROSES ULTRASONIC MILLING PADA PARTIKEL HYDROMAGNESITE[The Influence of Suspension Media on Ultrasonic Milling Process in Particle Hydromagnesite] - Sulistiyono, Eko; Manaf, Azwar; Firdiyono, F (Jurnal Metalurgi, 2012)
Research activities have been done to make nano size particles of hydromagnesite from dolomite mineral with ultrasonic milling equipment in the aquabident media or ethanol abosulte media or ethylene glycol media. In the research work the raw material of hydromagnesite was obtained from the extraction process of dolomite mineral with partial calcination, hydrationand carbonization processes. The first step of the process was runin 40 minute. The first experimental result showed that the best contotion of ultrasonic millingprocesswas in the ethylene glycol media. It can be evidenced from the increasing of temperature and result of SEM anaslysis. The final result can be concluded that in the ethylene glycol media can produced nano particle size of hydromagnesite e e e in the suspension. Particle size analysis using Delsa Nano shown that the process wich will held in ethylene glycol media with 16 minute for run time will produce that best size (23 – 95) nm.